BABY PYELOPLASTY VIA MINI FLANK INCISION- A SINGLE-CENTRE STUDY (The Research of Medical Science Review, 2025)
Background: Pelviureteric junction obstruction (PUJO) is a common problem in the field of pediatric urology. It is the most common cause of antenatal hydronephrosis. In those patients where surgical intervention is required, the mainstay management option is dismembered pyeloplasty. Objective: To evaluate the clinical effects and safety outcomes of early open pyeloplasty in children ≤ 3 years of age for the treatment of pelviureteric junction obstruction. Methodology: This prospective interventional cross-sectional study was conducted at Tabba Kidney Institute over six months during 16th August 2024 to 16th February 2025 on 50 children aged ≤3 years with clinically and radiologically diagnosed PUJO. Only primary PUJO cases without prior surgeries were included. Anderson-Hynes dismembered pyeloplasty was performed via a ≤2.5 cm mini flank incision. DJ stents were removed after four weeks. Statistical analysis was done using SPSS 23. Results: The mean age was 4.92 ± 2.8 months; 72% were male. Most cases involved the left kidney. Postoperative imaging showed reduced hydronephrosis (p <0.0001), and weight increased significantly. Crossing vessels were identified in 4% of cases. Conclusion: Mini open pyeloplasty is safe, effective, and minimally invasive approach for the management of PUJO in young children with least postoperative complications and successful surgical outcomes. The clinical findings that were observed from this study were consistent with pyeloplasty as the first-line surgical intervention for this ailment.